(untitled) (Journal of Philosophy Culture and Political Science, 2021)
The article examines the issues of the effectiveness of the use of non-violence in modern society. At all times and today in the 21st century, in all spheres of life, in different regions of the globe, clashes, crises, and wars occur. Despite the fact that the overall scale of wars has decreased, this carries significant negative damage to any society. At the same time, the potential of the latest technologies is being increasingly used instead of traditional means of war. And, although a peaceful situation prevails in the world as a whole, humanity is in a deep crisis. The endless struggle calls into question the future of humanity in general. Today, humanity needs to rise to a new level of consciousness and re-evaluate a number of vital issues. The qualitative and systemic development of society and various institutions depends on the ability to develop creatively, not destructively. Despite the fact that the philosophy of nonviolence was born in antiquity, there are few examples of its application in the history of social and political life. Modern research shows that the principles of non-violence can be used to achieve specific goals, and the practice of non-violence is much more effective than the use of force. Key words: violence, pacifism, peaceful world, violence, global peace, man.